Independent community libraries an exploratory study - Oida, Archimedes P. (2014)
Government creation of public libraries for the people have been lacking in the Philippines, however one little studied way that this is addressed is by communities forming libraries of their own independent of the state. A study of this is thus warranted in order to more fully understand and take advantage of this phenomenon.